(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
The increasing incidence of vehicle thefts, coupled with the rising need for advanced transportation solutions, has prompted significant advancements in the development of intelligent vehicle security systems. This paper outlines the design and execution of an IoT-based Vehicle Tracking and Theft Detection System, which incorporates GPS, GSM, ESP8266, a motor control mechanism, a switch-based intrusion detection system, and a buck converter for power management. The system aims to deliver real-time location tracking and proactive theft detection at an affordable price, making it suitable for widespread use in both personal and commercial vehicles. The system was prototyped and evaluated in real-world scenarios to assess its responsiveness, accuracy, and reliability. The findings demonstrate that the system offers precise location tracking, prompt alert notifications, and effective motor disconnection in response to potential threats. In comparison to traditional systems, this solution presents a cost-effective alternative.